Effects of Psychosocial Stress on Subsequent Hemorrhagic Shock and Resuscitation in Male Mice. Issue 6 (June 2019) - Langgartner, Dominik; Wachter, Ulrich; Hartmann, Clair; Gröger, Michael; Vogt, Josef; Merz, Tamara; McCook, Oscar; Fink, Marina; Kress, Sandra; Georgieff, Michael; Kunze, Julia F.; Radermacher, Peter L.; et al.
Abstract: Background: Hypoxemia and tissue ischemia during hemorrhage as well as formation of oxygen and nitrogen radicals during resuscitation promote hyperinflammation and, consequently, trigger severe multi-organ failure (MOF). Individuals diagnosed with stress-related disorders or reporting a life history of psychosocial stress are characterized by chronic low-grade inflammation and a reduced glucocorticoid (GC) signaling. We hypothesized that exposure to chronic psychosocial stress during adulthood prior to hemorrhagic shock increases oxidative/nitrosative stress and therefore the risk of developing MOF in mice. Methods and Findings: To induce chronic psychosocial stress linked to mild immune activation and reduced GC signaling in male mice, the chronic subordinate colony housing (CSC) paradigm was employed. Single-housed (SHC) mice were used as controls. Subsequently, CSC and SHC mice were exposed to hemorrhagic shock following resuscitation to investigate the effects of prior psychosocial stress load on survival, organ function, metabolism, oxidative/nitrosative stress, and inflammatory readouts. An increased adrenal weight in CSC mice indicates that the stress paradigm reliably worked. However, no effect of prior psychosocial stress on outcome after subsequent hemorrhage and resuscitation could be detected. Conclusions: Chronic psychosocial stress during adulthood is not sufficient to promote hemodynamic complications, organ dysfunction, metabolic disturbances and did not increase the risk of MOF after subsequent hemorrhage and resuscitation. Intravenous norepinephrine to keep target hemodynamics might have led to a certain level of oxidative stress in both groups and, therefore, disguised potential effects of chronic psychosocial stress on organ function after hemorrhagic shock in the present murine trauma model. Abstract : Supplemental Digital Content is available in the text